Raciocínio com falsidades : um ensaio sobre conhecimento inferencial - Alves, Eduardo (2021)
The goal of this essay is to evaluate the claim that it is possible to acquire inferential knowledge from false belief. In order to do so, we explain the main problem and some preliminaries notions in the first chapter. In the second chapter, we evaluate the reasons against the possibility of knowledge from falsehood. In the final chapter, we examine the reasons for the possibility of knowledge from falsehood.